HUBUNGAN RIWAYAT KELUARGA DAN KONSUMSI ASAM FOLAT PADA IBU TERHADAP KEJADIAN GANGGUAN SPEKTRUM AUTISME PADA ANAK - Agung Dewangga Kusuma Yudha (2023)
This study is aimed at examining the relationship between family history and maternal folic acid consumption with the presence of autism in children. It is known that autism, as a heritable neurological developmental disorder, carries a higher risk in younger children in families with a history of autism. This research uses observational analysis with a case-control study design. The primary data used in this study was collected from 32 samples and analyzed through univariate and bivariate methods, with the bivariate Chi-Square analysis technique chosen. The results of this study indicate that the majority of children with autism are the third child in their family (36.8% of 19 case groups). There is a significant relationship between family history and the incidence of autism (P = 0.000; P < 0.05), as well as a significant association between maternal folic acid consumption during pregnancy and the incidence of autism (P = 0.017; P < 0.05). Based on these findings, this study suggests that family history and folic acid consumption are related to the occurrence of autism. Furthermore, the majority of autism cases occur in children who are born as the third child.